The importance of lymph node ratio for locoregional recurrence of squamous cell carcinoma of the tongue. Issue 7 (July 2017) - Safi, Ali-Farid; Grandoch, Andrea; Nickenig, Hans-Joachim; Zöller, Joachim E.; Kreppel, Matthias
Abstract: Introduction: Locoregional recurrence plays a key role in treatment failure of patients with squamous cell carcinoma of the tongue. In a large amount of studies lymph node ratio could be demonstrated as a promising parameter to stratify risk of patients with oral cavity cancer. However data on the influence of lymph node ratio on locoregional recurrence of tongue squamous cell carcinoma is very rare. Material and methods: Retrospective chart review of 130 patients with treatment naive squamous cell carcinoma of the tongue. Exclusion criteria were neoadjuvant chemoradiotherapy, perioperative death, N3 disease, unresectable disease, synchronous malignancy, follow up <3 months. Contingency tables and χ 2 -test were performed to analyze associations between clinicopathological features and recurrence. All statistic were 2-sided and a p -value <0.05 was considered as significant. Multivariate analysis was performed using binary logistic regression analysis. A cut off value of 6% for lymph node ratio was applied. Results: Significant correlations were found between locoregional recurrence and pathologic N-Classification (<0.001), UICC stage (<0.001), perineural invasion ( p = 0.025), grading ( p = 0.001), number of resected lymph nodes ( p = 0.007) and lymph node ratio ( p < 0.001). Multivariate analysis indicated lymph node ratio as solely independent risk factor for locoregional recurrence. Conclusions: Lymph node ratio may be an useful parameter to stratify risk of locoregional recurrence of patients with squamous cell carcinoma of the tongue. Thus lymph node ratio might help to improve diagnosis and therapy of affected patients.